2019
DOI: 10.1002/ange.201910467
|View full text |Cite
|
Sign up to set email alerts
|

Loading Photochromic Molecules into a Luminescent Metal–Organic Framework for Information Anticounterfeiting

Abstract: Stimuli-responsive photoluminescent materials have attracted considerable attention owingt ot heir potential applications in security protection because the information recorded directly in materials with static luminescent outputs are usually visible under either ambient or UV light. Herein, we realizer eversible information anticounterfeiting by loading ap hotoswitchable diarylethene derivative into al anthanide metal-organic framework (MOF). Light triggers the open-and closed-form isomerization of the diary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 104 publications
1
59
0
Order By: Relevance
“…[6][7][8] In particular, research on multicolor emitting chromophores is of fundamental importance, [9][10][11] as they can serve as key precursors in achieving advanced functions of signal generation, [12][13][14][15] information storage and processing, [16][17][18] displays, [19][20][21][22] optical imaging, [23][24][25] and anticounterfeiting. [26][27][28][29][30][31] Control of molecular switches has been demonstrated as an effective way to modulate the luminescence conversion processes of chromophores. [32][33][34][35] Research on external stimuli-triggered luminescence switching has also been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In particular, research on multicolor emitting chromophores is of fundamental importance, [9][10][11] as they can serve as key precursors in achieving advanced functions of signal generation, [12][13][14][15] information storage and processing, [16][17][18] displays, [19][20][21][22] optical imaging, [23][24][25] and anticounterfeiting. [26][27][28][29][30][31] Control of molecular switches has been demonstrated as an effective way to modulate the luminescence conversion processes of chromophores. [32][33][34][35] Research on external stimuli-triggered luminescence switching has also been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Photochromism in molecular systems refers to a photoinduced reversible transformation between two isomers having distinct absorption spectra. In addition to the color change, such a reaction is often accompanied with changes in some other physical/chemical properties such as fluorescence emission, geometry structure as well as chemical reactivity, et cetera, which gives it various applications in the fields of optical materials, memories, photoswitches and biological systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Motivated by their wide applications, several photochromic families such as azobenzenes, furylfulgides, spiropyrans, diarylethenes, et cetera, have been developed, in which the azobenzenes and furylfulgides change structures via Z / E isomerization while spiropyrans and diarylethenes transform between their open and closed forms via ring closing and opening reactions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many of the switching characteristics in the solution are not readily transferable to the solid state since the switching mechanism is hindered in a densely packed phase. One promising strategy to overcome this challenge is to confine photoswitchable guests in porous solids, such as zeolites, mesoporous silica, and metal‐organic frameworks (MOFs) [12–22] …”
Section: Introductionmentioning
confidence: 99%